Analysis of international shipping emissions reduction policy and China’s participation - Liu, Huirong; Mao, Zhengkai; Li, Xiaohan (Frontiers in Marine Science, 2023)
In addressing climate change, the shipping industry, which is regarded as one sector that cannot be ignored in controlling greenhouse gas emissions, has become a key area of concern for the international community to achieve emissions reduction targets. The International Maritime Organization—the body that regulates international shipping—as well as the European Union and other international entities have adopted a series of emissions reduction policies, beginning a new era of shipping emissions reduction. In view of the urgency and complexity of this issue, the future policy direction of shipping emissions reduction and whether or not existing policies can achieve the emissions reduction targets have become the focus of attention in the global shipping industry. In addition, China’s dual identity as a shipping magnate and a developing country plays a crucial role in the development of shipping emissions reduction trends, reducing shipping emissions is necessary for China to achieve the “double carbon” commitment. Therefore, China should follow the trend, actively promote the decarbonization of the global shipping industry, scientifically plan its emissions reduction strategy, accelerate energy transformation, explore participation in the carbon emissions market, immediately promote the international unified shipping policy, and contribute the Chinese wisdom of green shipping and other domestic solutions to solve this global problem.